Subtle Differences in Active Site Structure between Bovine and Human Thrombins: ESR and Fluorescence Studies - Nienaber, Vicki L; Berliner, Lawrence J (Thrombosis and Haemostasis, 1991)
The primary structures of bovine and human a-thrombins are highly homologous yet their x-ray structures are not yet complete enough to distinguish differences. In order to probe and compare their dynamic conformations in solution, we examined bovine and human α-thombins with a series of active site directed fluorosul-fonylphenyl spin labeled inhibitors and fluorophores which probe a region within 10-15 Å of the catalytic serine residue. Overall, the nitroxide moieties were more immobilized in the bovine vs human derivatives reflecting either more apolar binding regions or steric obstructions to the motion of the nitroxide in bovine thrombin. Most of the labels which distinguish indole (apolar ligand) binding in human thrombin were found to display similar interactions in bovine thrombin, although slight differences in the general topography of this region were suggested. The two active site directed fluorophores, dansyl fluoride and p-nitrophenyl anthranilate showed differences in both λemmax and λexmax of the complexes with bovine and human-a-thrombin, respectively. Several of the effects observed i.e., ligand binding (indole or benzamidine) and the subtle hydrophobic interactions between the nitroxide moiety and the protein active site would be difficult to assess from an x-ray structure determination alone.